EFEKTIVITAS SISTEM AKUNTANSI PENJUALAN KREDIT : Credit Sales, Effectiveness, Credit Sales Accounting System. - Rusdiyanto, Rusdiyanto Rusdiyanto (Fakultas Ekonomi Universitas Gresik, 2021)
This study aims to determine the effectiveness of the credit sales accounting system applied to the credit sales accounting system at PT. XYZ. This type of research is a qualitative descriptive type with a case study approach and provides a picture between the subject and the object under study. In this case the research is intended to describe the credit sales accounting system. Based on the results of the study showed that the effectiveness of the credit sales accounting system applied at PT.XYZ is quite good, seen from the responsibility for the functions and authorities of each section and the achievement of a controlled credit sales accounting system in achieving company goals. But there are still a number of things that need to be fixed, such as the fact that there are still parts that run multiple functions in PT.XYZ.